Daya Antibakteri Bahan Tumpat Amalgam dan Resin Komposit Berfluor Terhadap Bakteri Streptococcus Mutans Serotipe KPSK2 - Dewa Ayu Nyoman Putri Artiningsih; Kamizar Kamizar (Faculty of Dentistry, Universitas Indonesia, 2015)
This research was carried out to study the difference in the antibacterial capacity of two kinds of filling materials, namely amalgam and composite resin, on S. mutans KPSK2 bacteria with different times of treatment. In total, 48 amalgam and composite resin samples each were prepared and then divided into four groups of treatment. Of each group, 6 samples were used to count the number of bacterial colonies and 6 samples to count the right obstacle zone. The results show that the best antibacterial capacity of composite resin occurred within one week, while for amalgam the best performance appears within one day. The antibacterial capacity of fluorine containing composites is stronger than that of amalgam for a time of 1 to 2 weeks.